Clinical and Genetic Analysis of a Family With Sitosterolemia Caused by a Novel ATP-Binding Cassette Subfamily G Member 5 Compound Heterozygous Mutation - Shen, Ming-fang; Hu, Ya-nan; Chen, Wei-xiang; Liao, Li-sheng; Wu, Min; Wu, Qiu-yan; Zhang, Jian-hui; Zhang, Yan-ping; Luo, Jie-wei; Lin, Xin-fu (Frontiers in Cardiovascular Medicine, 2022)
Sitosterolemia (OMIM ##210250), also known as phytosterolemia, is a rare autosomal recessive disorder caused by mutations in the ATP-binding cassette subfamily G member 5 (ABCG5) or member 8 (ABCG8) genes. This leads to abnormal functions of the transporter sterolin-1 protein encoded by ABCG5 and sterolin-2 protein encoded by ABCG8, respectively, which can hinder the formation of stable ABCG5/G8 heterodimers, decreasing its ability to transport sterols. As a result, phytosterols in tissue or plasma are significantly increased, leading to early onset atherosclerosis-related diseases and xanthelasma of tendons and skin. In this study, whole exome sequencing was performed on a Chinese Han proband with sitosterolemia to capture the target gene and screen for suspected pathogenic mutations. Sanger sequencing of the family members was performed to verify the relationship between family genetics and phenotypes. The structural and functional changes in the transporter sterolin-1 protein after the responsible mutation were predicted using bioinformatics analysis. A novel compound heterozygous mutation in the ABCG5 gene (NM_022436) was identified in a proband with sitosterolemia, one of which was inherited from the father: c.296T >G (p.M99R), and one from the mother: c.−76 C >T. SIFT, Polyphen2, and Mutation Taster software predicted that p.M99R may be the responsible variant and a novel variant. RNAFold software predicts that c.−76 C >T may affect the transcriptional information or the binding of RNA binding proteins by regulating the structure of RNA, and ultimately affect gene transcription or RNA stability and translation. Swiss model software predicts that the amino acid sequence around p.M99R is highly conserved, and p.M99R leads to instability of the tertiary structure of the ABCG5/ABCG8 heterodimer. GPS 5.0 predicted that M99R affects the phosphorylation of nearby amino acid sequences, and DUET and VarSite software predicted that M99R affects the stability of sterolin-1 and cause disease. The p.M99R and c.−76 C >T mutations led to the formation of unstable heterodimers, which disturbed sterol absorption and excretion in vivo. The compound heterozygous variants c.296 T >G (p.m99r) and C.−76 C >T on exon 3 of ABCG5 in this family may be the molecular genetic basis of sitosterolemia.